THE STATE OF PRACTICE OF TEACHING THE SUBJECT “MEDICAL BIOLOGY. GENERAL GENETICS” IN HIGHER MEDICAL EDUCATION INSTITUTIONS - Sharipova Farida Salimjanovna; Kulmatova Mavjuda Panji qizi (Bright Mind Publishing, 2025)
Decree of the President of the Republic of Uzbekistan dated April 20, 2017 No. PQ-2909 “On measures to further develop the higher education system” The main direction of the work being carried out to modernize the education system in the Republic of Uzbekistan is aimed at ensuring its efficiency, achieving new fundamental results, and adapting it to the needs of society. This, in turn, ensures that the achievements made in the field of education meet social requirements.